A 1.1-Mb Segmental Deletion on the X Chromosome Causes Meiotic Failure in Male Mice - Zhou, Jian (Society for the Study of Reproduction, Inc., 2013)
The mammalian X chromosome contains a large number of multicopy genes that are expressed during spermatogenesis. The roles of these genes during germ cell development and the functional significance of gene multiplication remain mostly unexplored, as the presence of multicopy gene families poses a challenge for genetic studies. Here we report the deletion of a 1.1-Mb segment of the mouse X chromosome that is syntenic with the human Xq22.1 region and contains 20 genes that are expressed predominantly in testis and brain, including three members of the nuclear export factor gene family (Nxf2, Nxf3, and Nxf7) and five copies of preferentially expressed antigen in melanoma-like 3 (Pramel3). We have shown that germline-specific Cre/loxP-mediated deletion of this 1.1-Mb segment is efficient and causes defective chromosomal synapsis, meiotic arrest, and sterility in male mice. Our results demonstrate that this 1.1-Mb region contains one or more novel X-linked factors that are essential for male meiosis.